Influence of Electrolyte Composition on the Semiconductor–Electrolyte Interface (SEI) Built-In for Enhanced Photoelectrochemical (PEC) Processes - Bartłomiej Leks; Aleksandra Parzuch; Nabila Nawaz; Justyna Widera-Kalinowska; Krzysztof Bienkowski; Renata Solarska (Molecules)
The relentless consumption of fossil fuels and soaring CO2 emissions have plunged the world into an energy and environmental crisis. As society grapples with these challenges, the demand for clean, renewable, and sustainable energy solutions has never been more urgent. However, even though many efforts have been made in this field, there is still room for improvement concerning efficiency, material stability, and catalytic enhancement regarding kinetics and selectivity of photoelectrochemical (PEC) processes. Herein, we provide the experimental proof for the enhancement of the photocurrent efficiency by the critical focus on semiconductor–electrolyte interface (SEI) properties. By tailoring electrolyte composition, researchers can unlock significant improvements in catalytic efficiency and stability, paving the way for advanced PEC technologies. In this study, we investigate the influence of electrolyte composition on SEI properties and its impact on PEC performance. By employing electrolytes enriched with carbonates, borates, sulphates, and alkali cations, we demonstrate their profound role in optimising photoelectrochemical CO2 reduction reaction (CO2RR) efficiency. Central to this work is Cu2O—an affordable, highly promising photocatalyst. While its potential is undeniable, Cu2O’s inherent instability and diverse reduction products, ranging from CH3OH to CO, HCOOH, CH3COOH, and CH3CH2OH, have hindered its widespread adoption in PEC CO2 reduction (CO2RR). Our approach leverages a straightforward yet powerful electrodeposition method, enabling a deeper exploration of SEI dynamics during photocatalysis. Key parameters, such as carbonate concentration, local pH, alkali cation presence, anionic geometry, CO2 solubility, and electrolyte conductivity, are systematically investigated. The findings reveal the formation of a unique “rigid layer” at the photocatalyst surface, driven by specific cation–anion interactions. This rigid layer plays a pivotal role in boosting PEC performance, offering a new perspective on optimising, among other PEC processes, CO2RR catalytic efficiency. This profound study bridges a critical knowledge gap, shedding light on the dual influence of cations and anions on SEI properties and PEC CO2RR. By unravelling these intricate interactions, we provide a roadmap for designing next-generation PEC systems. These insights pave the way for sustainable energy advancements, inspiring innovative strategies to tackle one of the most pressing challenges of our time.